Fetal Programming by Methyl Donors Modulates Central Inflammation and Prevents Food Addiction-Like Behavior in Rats - Cruz-Carrillo, Gabriela; Montalvo-Martínez, Larisa; Cárdenas-Tueme, Marcela; Bernal-Vega, Sofia; Maldonado-Ruiz, Roger; Reséndez-Pérez, Diana; Rodríguez-Ríos, Dalia; Lund, Gertrud; Garza-Ocañas, Lourdes; Camacho-Morales, Alberto (Frontiers in Neuroscience, 2020)
Fetal programming by hypercaloric intake leads to food addiction-like behavior and brain pro-inflammatory gene expression in offspring. The role of methylome modulation during programming on central immune activation and addiction-like behavior has not been characterized. We employed a nutritional programming model exposing female Wistar rats to chow diet, cafeteria (CAF), or CAF-methyl donor’s diet from pre-pregnancy to weaning. Addiction-like behavior in offspring was characterized by the operant training response using Skinner boxes. Food intake in offspring was determined after fasting–refeeding schedule and subcutaneous injection of ghrelin. Genome-wide DNA methylation in the nucleus accumbens (NAc) shell was performed by fluorescence polarization, and brain immune activation was evaluated using real-time PCR for pro-inflammatory cytokines (IL-1β, TNF-1α, and IL-6). Molecular effects of methyl modulators [S-adenosylmethionine (SAM) or 5-azatidine (5-AZA)] on pro-inflammatory cytokine expression and phagocytosis were identified in the cultures of immortalized SIM-A9 microglia cells following palmitic acid (100 μM) or LPS (100 nM) stimulation for 6 or 24 h. Our results show that fetal programming by CAF exposure increases the number of offspring subjects and reinforcers under the operant training response schedule, which correlates with an increase in the NAc shell global methylation. Notably, methyl donor’s diet selectively decreases lever-pressing responses for reinforcers and unexpectedly decreases the NAc shell global methylation. Also, programmed offspring by CAF diet shows a selective IL-6 gene expression in the NAc shell, which is reverted to control values by methyl diet exposure. In vitro analysis identified that LPS and palmitic acid activate IL-1β, TNF-1α, and IL-6 gene expression, which is repressed by the methyl donor SAM. Finally, methylation actively represses phagocytosis activity of SIM-A9 microglia cells induced by LPS and palmitic acid stimulation. Our in vivo and in vitro data suggest that fetal programming by methyl donors actively decreases addiction-like behavior to palatable food in the offspring, which correlates with a decrease in NAc shell methylome, expression of pro-inflammatory cytokine genes, and activity of phagocytic microglia. These results support the role of fetal programming in brain methylome on immune activation and food addiction-like behavior in the offspring.